2006
DOI: 10.1101/gad.1444406
|View full text |Cite
|
Sign up to set email alerts
|

Extensive post-transcriptional regulation of microRNAs and its implications for cancer

Abstract: MicroRNAs (miRNAs) are short, noncoding RNAs that post-transcriptionally regulate gene expression. While hundreds of mammalian miRNA genes have been identified, little is known about the pathways that regulate the production of active miRNA species. Here we show that a large fraction of miRNA genes are regulated posttranscriptionally. During early mouse development, many miRNA primary transcripts, including the Let-7 family, are present at high levels but are not processed by the enzyme Drosha. An analysis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
632
1
4

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 813 publications
(671 citation statements)
references
References 33 publications
28
632
1
4
Order By: Relevance
“…First, it has been reported that, during development and in tumors, the processing efficiency of pri-miRNAs is decreased. 32 However, the mRNA levels of Drosha and DGCR8 are not induced concordantly with the production of mature miRNAs. Post-translational regulation of DGCR8 activity mediated by dimerization and heme binding may explain this apparent discrepancy.…”
Section: Discussionmentioning
confidence: 95%
“…First, it has been reported that, during development and in tumors, the processing efficiency of pri-miRNAs is decreased. 32 However, the mRNA levels of Drosha and DGCR8 are not induced concordantly with the production of mature miRNAs. Post-translational regulation of DGCR8 activity mediated by dimerization and heme binding may explain this apparent discrepancy.…”
Section: Discussionmentioning
confidence: 95%
“…By contrast, the pri-form of the highly retinal-enriched miR-96/182/ 183 cluster is barely detectable even by RT-PCR, so abundance of some primiRNAs is unlikely to reflect general deficiencies in miRNA processing in retina . It is not yet clear what role, if any, these abundant primiRNAs may be playing in the retina, although high levels of other unprocessed pri-miRNAs have also recently been observed in embryonic tissue and cancer cells (Thomson et al, 2006), and this has led to the proposal that primiRNA processing by Drosha may be regulated in certain circumstances (Wulczyn et al, 2007). The recent discovery that activated Smads can associate with the Drosha complex and regulate its activity suggests a possible mechanism by which this could occur.…”
Section: Regulated Processing Of Retinal Pri-mirnas?mentioning
confidence: 99%
“…However, a majority of micro-RNAs are downregulated in tumor tissues, probably reflecting the cellular dedifferentiation generally associated with transformation (Lu et al, 2005). This downregulation is due at least in part to impairment of the microprocessor function (Thomson et al, 2006). Among these downregulated micro-RNAs, several have been shown to be bona fide tumor suppressors (Calin et al, 2002;Mayr et al, 2007;Welch et al, 2007;Bonci et al, 2008;Cole et al, 2008;Esquela-Kerscher et al, 2008;Chen et al, 2009;Trang et al, 2010).…”
Section: Introductionmentioning
confidence: 99%